Understanding Antecedents of Missed Nurse Care in Pediatric Ward Towards Nurse Outcome: A Descriptive Study in Indonesia - Marcella Amadea Widjaja; Ferdi Antonio (Riviera Publishing, 2026)
This research aims to examine the relationship between empowering leadership, performance-based evaluation, and resilience on nurse outcomes through self-efficacy, teamwork efficacy, and missed nursing care in paediatric wards, with the moderating role of cognitive empathy. This descriptive research was conducted during October 2024, utilising self-reported questionnaires. The research included 180 paediatric ward nurses, each with at least one year of working experience in paediatric wards where children were admitted. These nurses were selected from four private hospitals in one of the most populous provinces in Indonesia, West Java. The proposed model was tested using partial least squares structural equation modelling. The findings indicate that resilience, empowering leadership, and performance-based evaluation are significantly associated (p < 0.05; 95% CI) with paediatric nurses' outcomes from the nurses' perspective, mediated by nursing profession self-efficacy, nursing teamwork efficacy, and missed nursing care. As a moderating variable, cognitive empathy demonstrated a significant moderating role in the relationship between self-efficacy and missed nursing care (? = ?0.218) but was not significant for teamwork efficacy (? = 0.143). The proposed model demonstrated adequate prediction of paediatric nurse outcomes as the dependent variable (R² = 0.453). This research highlighted the importance of leadership styles that empower paediatric nurses, resilience-building programmes, and initiatives that enhance individual and team efficacy to mitigate missed nursing care in the paediatric ward. Hospital managers should prioritise strategies to improve leadership, resilience, and teamwork to enhance paediatric patient safety, care quality, and paediatric nurse well-being in hospital settings.